Clinical Outcomes Associated With Chronic Antimicrobial Suppression Therapy in Patients With Continuous‐Flow Left Ventricular Assist Devices. Issue 10 (20th January 2014) - Jennings, Douglas L.; Chopra, Anuvrat; Chambers, Rachel; Morgan, Jeffrey A.
Abstract This retrospective cohort study evaluates the effect of chronic antimicrobial suppression (CAS) therapy on clinical outcomes in patients with continuous‐flow left ventricular assist devices (CF‐LVADs) and a history of device‐related infection. Patients with CF‐LVAD implantation between January 2008 and August 2011 who received systemic CAS after index antibiotic treatment of a device‐related infection were included. Chronic suppression was defined as continuation of antibiotics for longer than 6 weeks after the index infection. Standard International Society for Heart and Lung Transplantation definitions were used. The primary outcome is failure of CAS, defined as a clinical deterioration resulting in the need for transition from oral to intravenous (IV) therapy or a need to change to a different IV antibiotic, elevation to status 1A on the transplant list as a result of ongoing infection, or device/driveline exchange. Of 140 patients screened, 16 patients were included (69% male, 63% African American, median age 52 years). The driveline was the most common site of infection (69%). Organisms isolated included Gram‐positive cocci (n = 7), Gram‐negative bacilli (n = 10), and Candida (n = 1). Oral trimethoprim/sulfamethoxazole treatment was most commonly used for suppression (37.5%). Failure of CAS occurred in 5/16 (31%) patients after a mean time of 175 days on therapy (range 10–598). The majority of failures (60%) required device exchanges. Side effects of nausea, vomiting, or diarrhea were reported in three patients; all required changes in oral suppression regimen. Clostridium difficile infection was noted in two patients. These results, which must be confirmed by a larger analysis, suggest that one‐third of CF‐LVAD patients may develop recurrent infections while on CAS therapy.